Projeto elétrico de uma usina de reciclagem de resíduos da construção civil em ambientes de mineração - TORRES, Gustavo Henrique dos Santos (2019)
The main objective of this work is the elaboration of a technical project of low voltage electrical installations, following the Brazilian standard NBR 5410 (Low Voltage Electrical Installations), aspects of NBR ISO / CE 8995-1 (Lighting of environments for the lighting design and the VALE Engineering Standardization System (SPE). The study project of this work is an RCC Plant that will be implemented in the Serra de Carajás. With the great demand for civil works and maintenance, the generation of large amounts of mineral waste occurs, so the RCC plant presents itself as an excellent alternative for the recycling of these wastes. The topics covered here are the stages of the elaboration of an electrical project, from the lighting design, through the lifting of load, dimensioning of the conductors and the protection devices, determination of the details of fixation of the equipment, going until the sizing of the energy supply power.